Individual Variation in Conditional β Cell Ablation Mice Contributes Significant Biases in Evaluating β Cell Functional Recovery - Lu, Song; Li, Jiatao; Lui, Kathy O. (Frontiers in Endocrinology, 2017)
Despite the βDTA (Ins2-rtTA; Tet-DTA) mice have been developed as a valuable tool to study β cell regeneration, their individual variation in therapeutic efficacy has not been characterized. Here, we demonstrated that the βDTA mice exhibited significant variations in both spontaneous and acquired β cell regeneration. We found that doxycycline (DOX)-induced β cell death was sufficient to cause polydipsia, translating even subtle difference in drinking habit into large variations in actual DOX intake among individuals within the same group. Accumulating evidence shows that transient expression of VEGFA enhances β cell functional recovery after injury. Therefore, we utilized the chemically modified mRNA (modRNA) technology to enable transient yet efficient VEGFA expression in the pancreas after DOX-induced β cell death. Surprisingly, under optimized DOX dose permissive of β cell regeneration, VEGFA modRNA only demonstrated marginal benefits on β cell functional recovery with large individual variations. We also revealed that the therapeutic efficacy of VEGFA modRNA on β cell regeneration was dependent on the degree of β cell loss induced by the accumulated DOX intake. Therefore, our results highlight a significant contribution of individual variation in the βDTA model and call for attention in evaluating potential efficacy of therapeutic agents in β cell regeneration studies.